Realistic and unrealistic direst costs in pharmacoeconomic anesthesia studies - Majstorović Branislava M.; Milaković Branko D. (Srpsko lekarsko drustvo, 2017)
Introduction: Multiplicity of anesthetic services and practice consume few resources individually, but collectively, they mean significant cost. Economic and pharmacoeconomic studies are done in order to rationalize resources. Aim: 1. To calculate the direct expense in anesthesia and reanimation; 2. To compare expenses to the price of anesthesia according to the unit prices of National Health Insurance Fund (NHIF); 3. To compare the duration of general anesthesia with costs in anesthesia departments. Methodology: This paper is a part of the retrospectively-prospective academic study of fourth phase carried out in the Clinical Center of Serbia. With permission of Ethical committee, we have set for 2005 and 2006, the direct cost of 148.876 anesthetic services in 11 departments of Clinical Center of Serbia as tertiary-type institution of medical health care. Research group included all patients of both sexes, children and adults. We compared the direct cost per minute of general anesthesia with average duration of anesthesia in every anesthesia department of surgical clinics. The direct cost was compared with the same, 'unit' prices of NHIF. The direct cost was compared with the same, 'unit' prices of RHIF. We have used linear and regression statistical product and service solutions model for component cost analysis /SPSS 15/. Results: Most budget resources are selected for the employees' sallaries (40%), then the medicines and supplies (31,80%) and the other expenses including the analysis and analytic devices (28,20%). Direct costs indicate a linear correlation and statistically marked difference p=0,012, F=9,270 compared to anesthesia duration indicating the coefficient of correlation r=0,694. Direct costs are highest considering longest segment of anesthesia. We have obtained linear correlation R=0,706 for direct costs excluding the neurosurgical anesthesia with 'unit prices'of anesthesia and anesthetic services indicating F=9,951 and p=0,01. Conclusions: Anesthesia and anesthetic services show statistically significant and financially significant correlation with the direct costs and duration of anesthesia within different surgical specialties. Cosidering direct costs, only the costs of anesthetic drugs and materials are realistic, and all other elements are determined by law and by contract with NHIF. Other costs, out of the direct costs group shall be theoretically reduced by running the analyzes required for anesthesia and for the planned surgical intervention in primary health care protection. Data base related to surgical data and better computer programs able to monitor multiple parameters during hospital treatment, could determine more precisely the value of anesthetic services.